Emily Carr: Border-crossing Canadian artist and writer - Bjørhovde, Gerd (Nordlit, 2014)
Emily Carr (1871–1945) is today generally considered one of Canada’s greatest and most unique artists. However, her recognition was a long time coming, and it was only towards the end of her life that fame came her way. The article discusses the critical reception of Carr’s work both as a painter and writer, paying particular attention to her border-crossing strategies in her use of indigenous/First Nations art and culture in her own work. Furthermore, it looks at the development of Carr’s art and its connection to the construction of a Canadian national identity, or Canadian-ness, in the early twentieth century.